Subjective and Objective Comparative Study of DAB+ Broadcast System - GILSKI, Przemyslaw; STEFAŃSKI, Jacek (Archives of Acoustics, 2017)
Broadcasting services seek to optimize their use of bandwidth in order to maximize user’s quality of experience. They aim to transmit high-quality digital speech and music signals at the lowest bitrate. They intend to offer the best quality under available conditions. Due to bandwidth limitations, audio quality is in conflict with the number of transmitted radio programs. This paper analyzes whether the quality of real-time digital DAB+ broadcasted radio programs surpasses the quality offered by analog FM radio. We also perform a subjective and objective quality assessment comparative study of the HE-AAC v2 audio codec used in DAB+. The subjective studies were carried out using the MOS test methodology, whereas the objective tests were realized using the ViSQOLAudio metric. These studies were followed by a questionnaire concerning the migration from analog to digital radio domain.